Collaborative Governance dalam Pengembangan Kampung Wisata Kelurahan Keprabon Kecamatan Banjarsari - Khamid, Luthfi; Suwardi, Suwardi; Haryanto, Aris Tri (JI@P, 2025)
The results of the Collaborative Governance study in the development of the Keprabon Village Tourism Village were carried out with several things, namely: 1) Face-to-face dialogue as a communication tool in collaboration in developing tourist villages in Keprabon Village is very important for building trust, solving problems together, and designing effective strategies. Local communities involved in this dialogue will feel ownership and responsibility for tourism development, which in turn will strengthen the sustainability of the tourism village. 2) Building trust in collaborative tourism village development in Keprabon Village is a process that requires open communication, active community involvement, consistency in action, and commitment to project sustainability. Well-built trust will enable all parties to work together more effectively and realize inclusive and sustainable tourism village development. This trust must be continuously fostered through transparent and accountable management, as well as respect for existing local wisdom. 3) Commitment to process in collaborative tourism village development in Keprabon Village is very important for the success of this project. All parties involved must have the same awareness of the importance of carrying out the process with full responsibility, from planning to evaluation. This will ensure that tourism village development can take place in a coordinated manner, overcome emerging challenges, and provide sustainable benefits for the community, government, and private sector. Keywords: Collaborative Governance Tourism Village